SASTRA DAN NILAI KEARIFAN LOKAL DALAM TANTANGAN GLOBAL - Kadir, Herson (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Projected values of local wisdom in literary works can be a controlling attitude in global society. Through literary works, it can be obtained moral and ethical values that have been filtered through civilization of a cultured society. Literature is able to present knowledge and information, insight, precise and valuable experience, and educated through various types of literary works such as novels, short stories, poetry and drama. All of these values contains values, including local wisdom. Values that derived from local wisdom can serve as values of moral character and values of moral performance. These values are very important to know, studied, discovered, and transferred through educational activities. In the field of education, the delivery of local wisdom values in literary works can be created through teaching and learning in classroom, family, and other appreciative activitiesin society. The value of local wisdom can be used as moral and performance character that are needed in facing global challenges. The influence of globalization reflects the changes of time and space concepts and the existence of cultural interactions. Therefore, literature plays an important role in spinning understanding of soul, character, culture, and social civilization into a power and force in facing the globalization. So that, the kindness values contained based on local wisdom in literary works have to be well explored, elaborated, transformed and communicated to public through the support of all parties. Keywords— literature, values, local wisdom, global